Hemorrhages of the first half of pregnancy - Guevara Ríos, Enrique (2015)
This is a review on the etiology of hemorrhage in the first half of pregnancy, including abortion, ectopic pregnancy, and trophoblastic disease, in reference to definition, clinical presentation and treatment of these complications.